LINGUISTIC AND COGNITIVE ANALYSIS OF SPORTS DICOURSE - Khaydarova Gavkhar Abdukadirovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
The article examines the interaction between language and thought in the stressful context of sports interviews. It investigates how athletes and coaches simultaneously control speech, memory, emotions, and public image using concepts from linguistics and cognitive science. Moreover, it emphasizes typical linguistic elements such as fillers, repetition, short or incomplete sentences, and polite strategies that reflect mental effort.